Organizing women workers in the informal economy : beyond the weapons of the weak - Kabeer, Naila; Sudarshan, Ratna M.; Milward, Kirsty (London Zed books, 2013)
Organizing Women Workers in the Informal Economy explores the emergence of an alternative repertoire among women working in the growing informal sectors of the global South: the weapons of organization and mobilization. This crucial book offers vibrant accounts of how women working on farms, as sex workers, maids, and waste pickers, in fisheries and factories, have come together to carve out new identities for themselves, define what matters to them, and develop collective strategies of resistence and struggle. -- Book Jacket.
Introduction: Beyond the weapons of the weak: organizing women workers in the informal economy / Naila Kabeer, Kirsty Milward and Ratna Sudarshan -- Understanding the dynamics of an NGO/MBO partnership: organizing and working with farm women in South Africa / Colette Solomon -- Organizing for life and livelihoods in the mountains of Uttarakhand: the experience of Uttarakhand Mahila Parishad / Anuradha Pande -- Negotiating patriarchies: women fisheries workers build SNEHA in Tamil Nadu / Jesu Rethinam -- "If you don't see a light in the darkness, you must light a fire": Brazilian domestic workers' struggle for rights / Andrea Cornwall with Creuza Maria Iliveira and Terezinna Gonçalves -- The challenge of organizing domestic workers in Bangladore; caste, gender and employer-employee relations in the informal economy / Geeta Menon -- Power at the bottom of the heap: organizing waste pickers in Pune / Lakshmi Naraya and Poornima Chikarmane -- Sex, work and citizenship: the VAMP sex workers' collective in Maharashtra /Meena Seshu -- Gender, ethnicity and the illegal 'other': women from Burma organizing women across borders / Jackie Pollock -- End note: Looking back on four decades of organizing the experience of SEWA / Ela Bhatt.
Includes bibliographical references and index.
Keywords: Women -- Employment; Women in development; Informal sector (Economics); Informal sector (Economics); Women -- Employment; Women in development; Frauenarbeit; Schattenwirtschaft